Isolation and functional analysis of CONSTANS-LIKE genes suggests that a central role for CONSTANS in flowering time control is not evolutionarily conserved in Medicago truncatula - Wong, Albert C. S.; Hecht, Valérie F. G.; Picard, Kelsey; Diwadkar, Payal; Laurie, Rebecca E.; Wen, Jiangqi; Mysore, Kirankumar; Macknight, Richard C.; Weller, James L. (Frontiers in Plant Science, 2014)
The zinc finger transcription factor CONSTANS has a well-established central role in the mechanism for photoperiod sensing in Arabidopsis, integrating light and circadian clock signals to upregulate the florigen gene FT under long-day but not short-day conditions. Although CONSTANS-like (COL) genes in other species have also been shown to regulate flowering time, it is not clear how widely this central role in photoperiod sensing is conserved.Legumes are a major plant group and various legume species show significant natural variation for photoperiod responsive flowering. Orthologs of several Arabidopsis genes have been shown to participate in photoperiodic flowering in legumes, but the possible function of COL genes as integrators of the photoperiod response has not yet been examined in detail. Here we characterize the COL family in the temperate long-day legume Medicago truncatula, using expression analyses, reverse genetics, transient activation assays and Arabidopsis transformation. Our results provide several lines of evidence suggesting that COL genes are unlikely to have a central role in the photoperiod response mechanism in this species.